Experiences of Supervision at Practice Placement Sites. (24th August 2014) - Diack, Lesley; Gibson, Kathrine; Munro, Kim; Strath, Alison
Abstract : Background . Whilst placement supervision and clinical education programmes are of significant value in shaping the behaviours of undergraduate healthcare students, appropriate provisions which are efficacious to the learner are somewhat lacking, particularly for students studying on UK MPharm programmes. Objectives . To explore and explain the value of placement supervision to the personal development and employability of undergraduate pharmacy students. Methods . Students participated in a week long community pharmacy pilot programme, a result of a collaborative effort between the School of Pharmacy and Life Sciences and a small consortium of community pharmacies. Students and stakeholders were asked to evaluate their experiences via separate questionnaires which had been developed to elicit views and attitudes. Key Findings . Feedback from students and stakeholders towards the experience was overwhelmingly positive with multiple benefits being reported. Of particular prominence was the emphasis in student feedback on the value of placement supervision to their professional and personal development. Findings were indicative of a development in clinical practice proficiencies, core skills, and improvement in decision-making practice. Conclusions . The benefits of clinical supervision to the professional and personal development of MPharm students are well documented, although attracting professional pharmacy supervisors is proving a problematic task for educational providers in the UK.